2014
DOI: 10.9734/bbj/2014/7659
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting Filamentous Fungi for Amylase Production: Standardization of Aspergillus japonicus Culture Conditions

Abstract: Aims: Prospecting different filamentous fungi for high production of amylases in standard conditions for future application in biotechnology industries. Methodology: Samples were collected in different field areas in the state of Bahia, Brazil, for isolating filamentous fungi. Fungi were grown in Petri dishes in a culture medium containing 4% Quaker® oatmeal and 2% bacteriological agar. Fungi screening was carried out in liquid medium containing 1% starch at 30°C and pH6.0 under static conditions for 4 days. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
10
0
4
Order By: Relevance
“…The characteristics of the β-glucosidase produced by A. japonicus have been previously assessed for a potential use in biomass saccharification (Korotkova et al 2009). Pasin et al (2014) reported high levels of amylase activity in A. japonicus when cultivated in different agro-industrial residues. The presence of this activity in the cultures might be due to the fact that amylases are constitutive enzymes, which are generally located in the fungal cell walls (Benassi et al 2012).…”
Section: Enzymesmentioning
confidence: 99%
“…The characteristics of the β-glucosidase produced by A. japonicus have been previously assessed for a potential use in biomass saccharification (Korotkova et al 2009). Pasin et al (2014) reported high levels of amylase activity in A. japonicus when cultivated in different agro-industrial residues. The presence of this activity in the cultures might be due to the fact that amylases are constitutive enzymes, which are generally located in the fungal cell walls (Benassi et al 2012).…”
Section: Enzymesmentioning
confidence: 99%
“…O aumento de infecções microbianas e a resistência dos patógenos a medicamentos disponíveis no mercado tem despertado grande interesse na pesquisa por novas drogas de origem vegetal (JENSEN et al, 2015 (UMAR et al, 2016). Em concordância com os resultados desta pesquisa, autores citam que o extrato etanólico das cascas dos frutos de romã é capaz de inibir o crescimento da espécie Staphylococcus aureus (MOREIRA et al, 2014).…”
Section: Resultados E Discussõesunclassified
“…O Brasil é um dos países com maior diversidade de organismos vivos, incluindo os fungos filamentosos que são encontrados em abundância nos distintos habitats (PEREIRA, 2017). A prospecção de fungos filamentos vem se destacando, visto que estes representam uma rica fonte em recursos genéticos para aplicação em inúmeros processos e produtos biotecnológicos (PASIN, 2014). O uso das enzimas se destaca entre os metabólitos fúngicos explorados.…”
Section: Introductionunclassified